Sustainability as a Competitive Tool for the Brave? Or for the Best? A Behavioral Theory Perspective. (September 2020) - Bettinazzi, Emanuele L. M.; Massa, Lorenzo; Neumann, Kerstin
Who invests in sustainability as a strategic choice? We adopt a behavioral theory perspective to explain the heterogeneity of sustainability-driven investments. Building on problemistic search and organizational inertia arguments, and contrary to resource-based explanations, we argue that a firm's competitiveness might actually reduce its likelihood to invest in sustainability. We also propose that less competitive firms invest in sustainability to improve their economic situation and, thus, that this choice results in positive performance effects. We further theorize that a firm's level of commitment to its stakeholders will strengthen its likelihood to invest in sustainability. In a sample of 780 North American public companies in the period from 2007 to 2011, we find evidence to support our proposed model. Based on our findings, we draw implications for the further study of the behavioral roots of strategic change as well as for sustainability-oriented managerial practice and policy making.